2007
DOI: 10.1158/0008-5472.can-07-0127
|View full text |Cite
|
Sign up to set email alerts
|

MPC-6827: A Small-Molecule Inhibitor of Microtubule Formation That Is Not a Substrate for Multidrug Resistance Pumps

Abstract: A novel series of 4-arylaminoquinazolines were identified from a cell-based screening assay as potent apoptosis inducers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 23 publications
5
94
0
Order By: Relevance
“…CA4P has progressed through to phase III clinical trials, and AVE8062 (Sanofi-Aventis) has been reported to be in phase III evaluation for advanced-stage soft tissue sarcoma after failure of anthracycline and ifosfamide chemotherapies (trial NCT00699517). Other compounds include OXi4503 (14), NPI-2358 (15), CYT-997 (16), MPC-6827 (17), and EPC2407 (18,19). These latter agents have completed phase I evaluation and are under evaluation in phase II trials.…”
Section: Discussionmentioning
confidence: 99%
“…CA4P has progressed through to phase III clinical trials, and AVE8062 (Sanofi-Aventis) has been reported to be in phase III evaluation for advanced-stage soft tissue sarcoma after failure of anthracycline and ifosfamide chemotherapies (trial NCT00699517). Other compounds include OXi4503 (14), NPI-2358 (15), CYT-997 (16), MPC-6827 (17), and EPC2407 (18,19). These latter agents have completed phase I evaluation and are under evaluation in phase II trials.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, MPC-6827 is potent at low nanomolar concentrations in multiple cancer types, including pancreas, prostate, breast, colon, non-small cell lung, small cell lung, ovarian, and brain cancers, melanoma, and leukemia. In cell lines overexpressing multidrug resistance pumps, the activity of MPC-6827 is similar to that in nonresistant cell lines, suggesting that it should be active against multidrugresistant tumors (1,2). In vivo, MPC-6827 significantly inhibits the growth of various subcutaneously implanted tumor lines (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…In cell lines overexpressing multidrug resistance pumps, the activity of MPC-6827 is similar to that in nonresistant cell lines, suggesting that it should be active against multidrugresistant tumors (1,2). In vivo, MPC-6827 significantly inhibits the growth of various subcutaneously implanted tumor lines (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations